Strategies and Policies To Increase Competitiveness of Cassava in Lampung Province, Indonesia - Teguh, Teguh Endaryanto; Wan Abbas Zakaria; Lidya Sari Mas Indah; Amanda Putra Seta (Jurnal Manajemen & Agribisnis, 2022)
Cassava is an important commodity and has a strategic role for the Indonesian economy, especially for Lampung Province as the main producer. However, prices and provitas that tend to be low, policies are not in favor of farmers, and weak institutions, so the commodity's is low competitiveness. Government intervention in encouraging the competitiveness of a commodity by providing protection to producing farmers is felt to be very effective, especially for cassava commodities. Therefore, this study aims to analyze appropriate strategies and policies in increasing the competitiveness of cassava commodities in Lampung Province. Therefore, strategies and policies are needed to increase the competitiveness of cassava commodities in Lampung Province. The research was conducted in 2020 in Central Lampung and East Lampung Regencies with a total of 120 farmers as respondents. This research uses policy matrix analysis or PAM analysis and qualitative descriptive. The results showed that cassava has comparative and competitive advantages even though it is low. Therefore, the best policy is needed to increase the competitiveness of cassava commodities. The policy in order to increase the competitiveness of cassava in Lampung Province can be done by increasing output by 20% even though the cost of fertilizer increases by 20%. Some of these policies and strategies can have an impact on production cost efficiency, improve the quality of cassava, increase the quantity of cassava, and increase the income of cassava farmers. Keywords: cassava, competitiveness, improvement policy, PAM, strategy